2021
DOI: 10.3389/ijph.2021.585801
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life Profiles in Dialyzed Patients With Varying Health Literacy. A Cross-Sectional Study on Slovak Haemodialyzed Population

Abstract: Objectives: Chronic kidney disease (CKD) strongly affects patients’ health-related quality of life (HRQoL), mostly in the advanced stages of CKD. Health literacy (HL) may affect this association, in particular for some aspects of HRQoL. The aim of this study is to compare the profiles of HRQoL in dialyzed patients with varying HL.Methods: We obtained data on HL using the Health Literacy Questionnaire (HLQ) and on HRQoL using the Kidney Disease Quality of Life – Short Form (KDQoL-SF 1.3) in a multicentre cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…Sound social functioning is an objective reflection of an individual’s QoL; and defective social functioning can lead to disorder in the individual’s social function and social behavior dysfunction ( 71 ). Enabling people with MHD to function and behave socially in accordance with their role in society can help build confidence in overcoming their illness and is essential to improving their QoL ( 33 ). Thus, social functioning becomes one of the intermediate mechanisms linking SES and HRQoL, i.e., differences in SES can lead to inequalities in HRQoL through social functioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sound social functioning is an objective reflection of an individual’s QoL; and defective social functioning can lead to disorder in the individual’s social function and social behavior dysfunction ( 71 ). Enabling people with MHD to function and behave socially in accordance with their role in society can help build confidence in overcoming their illness and is essential to improving their QoL ( 33 ). Thus, social functioning becomes one of the intermediate mechanisms linking SES and HRQoL, i.e., differences in SES can lead to inequalities in HRQoL through social functioning.…”
Section: Discussionmentioning
confidence: 99%
“…SES is not only an independent predictor of HRQoL in MHD patients ( 31 ) but also the primary factor affecting patients’ illness perceptions ( 32 ) and social functioning ( 33 ). The effect of SES on patients’ HRQoL is not always straightforward and is often mediated by psychological factors ( 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…The potential of communication-related inventions to enhance understanding among those with HL limitations and positive impact on clinical outcomes has fueled a rapid expansion of research on HL, especially in populations with chronic diseases [ 20 ]. It is known that limited HL is associated with less efficient use of health services in the general population, greater difficulty in the medication's compliance, poorer quality of life, and a higher mortality [ 20 , 21 ]. A systematic review was published in 2018 that included 29 studies with a total of 18 300 patients (4367 non-dialysis CKD; 13 202 dialysis; 390 kidney transplants; 341 unspecified) reporting solid evidence of the causal effects of literacy in health on the results of patients with CKD, suggesting associations with adverse clinical events, increased healthcare use and mortality [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is a multidimensional factor that covers several competencies related to searching for health information, self-management and cooperation with healthcare providers [ 24 ]. Low HL is common in dialysed patients [ 25 , 26 ] and is associated with poorer HRQoL [ 27 , 28 , 29 ]. All aforementioned studies reported significant associations of low HL with poorer mental and physical HRQoL in dialysed patients [ 27 ] and also in patients in earlier stages of the disease (3–5 stage) [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…All aforementioned studies reported significant associations of low HL with poorer mental and physical HRQoL in dialysed patients [ 27 ] and also in patients in earlier stages of the disease (3–5 stage) [ 28 ]. Our previous study [ 29 ] added to this evidence by providing detailed profiles of HRQoL in dialysed patients by level of HL.…”
Section: Introductionmentioning
confidence: 99%